I want to go home! - Ross, Tony (London : Andersen Press, 2014)
The Little Princess has been moved to a new castle, where there is lots more room! But she just wants to go home to the old castle. But is the old castle still the same, now that it has new owners' A wonderfully funny and reassuring book that will ring true with anyone who has ever moved house with a toddler.
Keywords: Children's stories Pictorial works s -- Juvenile work